2013
DOI: 10.3233/oer-130212
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with live fire training: Buildup of heat stress and fatigue, recovery and role of micro-breaks

Abstract: Background: Forty five percent of on-duty firefighter deaths every year are cardiovascular (CV) related. Heat stress and fatigue buildup are two common occupational risk factors for firefighters. These risk factors may increase the firefighters' chances of having cardiac events or even death. Objective: Buildup of heat stress and fatigue in firefighters and their recovery from these stresses during live-fire training exercises was investigated. Methods: Twenty full time firefighters, from two different fire-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Experimental data from the previous studies describing a firefighting training drill were used to develop the human whole body computational model. A typical training drill consisted of alternating firefighting scenarios and rest periods [28,29]. The firefighting scenarios consisted of (1) search for the origin of flame, (2) hose advancement, and (3) search and rescue of the victim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data from the previous studies describing a firefighting training drill were used to develop the human whole body computational model. A typical training drill consisted of alternating firefighting scenarios and rest periods [28,29]. The firefighting scenarios consisted of (1) search for the origin of flame, (2) hose advancement, and (3) search and rescue of the victim.…”
Section: Methodsmentioning
confidence: 99%
“…The firefighting scenarios consisted of (1) search for the origin of flame, (2) hose advancement, and (3) search and rescue of the victim. De-identified datasets including the heart rate, experimental core body temperature ( T c_E ), and physiological details of a single firefighter (age = 33 yr, weight = 86.7 kg) were obtained from Mani et al [29] and used in this study. The experimental study, conducted by Mani et al [29], was approved by University of Cincinnati Institutional Review Board and the firefighter provided informed consent prior to participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The human subject data of firefighter 2 and firefighter 3 were obtained during firefighting training drills in the study reported by Mani et al [17], which was performed with the approval of the University of Cincinnati Institutional Review Board. The Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These drills consisted of alternating periods of firefighting and rest scenarios. The de-identified datasets included the heart rate, the experimental core body temperature, T c_E , and the physiological parameters of firefighters 1, 2, and 3 [16,17]. Additional details such as the age and weight of the firefighters are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Literature provides two models for predicting hyperthermia (core temperature >100.4°F): (a) one based on physiology of heat stress (Yokota, Berglund, Santee, Butler, & Hoyt, 2005; Yokota, Berglund, & Bathalon, 2012; Yokota, Berglund, Santee, et al, 2012) and (b) data-driven decision trees (Mani, Rao, James, & Bhattacharya, 2015). Use of such predictive modeling has a critical role in designing and developing innovative interventions to minimize heat stress in the working population of all ages in hot environments (Mani et al, 2013, 2015), such as firefighters and agricultural and construction workers.…”
Section: Discussionmentioning
confidence: 99%